Instability of the shoulder in athletes - Zumstein, M. A.; Jost, B.; Gerber, C. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 2005)
This article reviews diagnostic and therapeutic concepts in athletes with a first time shoulder dislocation or with shoulder instability based on the authors` experience and the recent literature. In general, following a first anterior dislocation the shoulder should be immobilized in adduction and 10° external rotation splint for 6 weeks. Surgical shoulder stabilization is probably only indicated in the very young active patient who is dependent on the use of the arm in an overhead abduction-external rotation position like throwers at the end of the season or in individuals where very high risks are involved in recurrence. In chronic instability, both laxity and instability must be determined clinically and a possible bony lesion assessed with (Arthro-) CT scan. Arthroscopic stabilization using suture anchor techniques seems to be the treatment of choice in the chronic anterior shoulder instability. However, in patients with bony lesions of the anterior-inferior glenoid rim and in revision surgery we perform the Latarjet-Bristow procedure which includes a transfer of the coracoid process on the anterior glenoid neck.